Tensioned flexible riser vibrations under wave excitation, an investigation on the scale effect - Feng, Yunli; Li, Sunwei; Chen, Daoyi (Frontiers in Marine Science, 2024)
In order to study the scale effect in wave-structure interactions and the role that structure-related parameters (tension T or bending stiffness EI) plays, riser model tests under regular waves were conducted using the model with multiple geometric scales (1:15, 1:12 and 1:9) in a wave basin. The riser model used is a novel structural design combing the outer polyvinyl chloride pipe with the core steel rod which could be simplified as a cantilever beam. Different initial tension T acting on the riser are tested by adjusting the slotted weight. The results show that the amplitude varies in a cubic fashion with the distance from the fixed end. In addition, the influence of the wave period and top tension T on the amplitude are investigated, which ultimately leads to a dimensionless number π1 = KCd·TL2/EI where KC is the classical Keulegan–Carpenter number (KC), EI shows the bending stiffness of the riser model and L gives the pipe length. With the KC number revised to take the distance from the fixed end into the calculation, this parameter provides a good measure in estimating the amplitudes of the riser vibrations induced by the waves.